Pressure Transient Analysis and Flux Distribution for Multistage Fractured Horizontal Wells in Triple-Porosity Reservoir Media with Consideration of Stress-Sensitivity Effect - Jingjing Guo; Haitao Wang; Liehui Zhang; Chengyong Li (Journal of Chemistry)
Triple-porosity model is usually adopted to describe reservoirs with multiscaled pore spaces, including matrix pores, natural fractures, and vugs. Multiple fractures created by hydraulic fracturing can effectively improve the connectivity between existing natural fractures and thus increase well deliverability. However, little work has been done on pressure transient behavior of multistage fractured horizontal wells in triple-porosity reservoirs. Based on source/sink function method, this paper presents a triple-porosity model to investigate the transient pressure dynamics and flux distribution for multistage fractured horizontal wells in fractured-vuggy reservoirs with consideration of stress-dependent natural fracture permeability. The model is semianalytically solved by discretizing hydraulic fractures and Pedrosa’s transformation, perturbation theory, and integration transformation method. Type curves of transient pressure dynamics are generated, and flux distribution among hydraulic fractures for a fractured horizontal well with constant production rate is also discussed. Parametric study shows that major influential parameters on transient pressure responses are parameters pertinent to reservoir properties, interporosity mass transfer, and hydraulic fractures. Analysis of flux distribution indicates that flux density gradually increases from the horizontal wellbore to fracture tips, and the flux contribution of outermost fractures is higher than that of inner fractures. The model can also be extended to optimize hydraulic fracture parameters.